The Oxford handbook of participation in organizations - Wilkinson, Adrian, 1963- (Oxford University Press, 2010)
Employee participation encompasses the range of mechanisms used to involve the workforce in decisions at all levels of the organization. This handbook looks at the different arguments and schools of thought, with the aim of analysing them, not just in terms of implementation but also principles.